Creencias sobre estereotipos de género de jóvenes universitarios del norte de México (2016)
The purpose of this study was to analyze the beliefs about social gender assessments in a college student population, in order to know the changes that these beliefs undergo. A sample of 1.921 students of both sexes of two public universities in northern Mexico, located in the cities of Hermosillo, Sonora and Saltillo, Coahuila, completed a scale of gender stereotyped beliefs. Five dimensions were explored: Femininity / masculinity, maternity / paternity roles, sexuality, skills and abilities, and expressions of emotion / aggression. The results indicate greater attachment to traditional positions in men and in Engineering students. In general, all students irrespective of semester have the same gender biases. It is recommended that the gender perspective be transversalised in higher education institutions through awareness and training programs.